2005
DOI: 10.1136/ard.2004.022582
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in combination with methotrexate in active ankylosing spondylitis: a clinical and imaging study

Abstract: Objective: To examine the efficacy and safety of infliximab combined with methotrexate compared with methotrexate alone in the treatment of ankylosing spondylitis (AS) using MRI and DXA to monitor its impact on bone. Methods: In this single centre study 42 subjects with active AS were treated with methotrexate and were randomly assigned, in a ratio of 2:1, to receive five infusions of either 5 mg/kg infliximab or placebo over 30 weeks. The primary outcome was improvement in disease activity as shown by the BAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 27 publications
4
75
0
3
Order By: Relevance
“…In this cohort, infliximab therapy resulted in significant suppression of MRI-determined inflammation relative to placebo, with a significant reduction in the total MRI score, increased resolution of inflammatory lesions, and decreased progression of new inflammatory lesions at week 16 ( Figure 1). These results are consistent with those seen in patients with established AS (18,22,29). Additionally, we observed impressive clinical responses to infliximab therapy, with improvement in disease activity, functional status, and quality of life seen at week 16.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this cohort, infliximab therapy resulted in significant suppression of MRI-determined inflammation relative to placebo, with a significant reduction in the total MRI score, increased resolution of inflammatory lesions, and decreased progression of new inflammatory lesions at week 16 ( Figure 1). These results are consistent with those seen in patients with established AS (18,22,29). Additionally, we observed impressive clinical responses to infliximab therapy, with improvement in disease activity, functional status, and quality of life seen at week 16.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in established AS have shown that patients with a shorter disease duration have a better response to anti-TNF agents (30), suggesting that very early treatment before damage is evident on radiographs will lead to improved responses. Therefore, this study confirms the efficacy of infliximab in early axial SpA and suggests that these patients may respond more favorably to infliximab treatment than patients with radiographically evident, established AS (18,22,29).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Several clinical studies have shown that etanercept reduces disease activity in patients with spondyloarthropathies, including reactive arthritis and AS [4][5][6][7][8]. Similar results have been reported with inXiximab, a chimeric monoclonal antibody against TNF [9][10][11][12][13][14][15]. The aim of the present work was to compare the eYcacy and safety of both etanercept and inXiximab in patients with ankylosing spondylitis in a two-year open label randomised study.…”
Section: Introductionsupporting
confidence: 59%